Using the biomarker cotinine and survey self-report to validate smoking data from United States Veterans Health Administration electronic health records. Issue 2 (26th May 2022) - McGinnis, Kathleen A; Skanderson, Melissa; Justice, Amy C; Tindle, Hilary A; Akgün, Kathleen M; Wrona, Aleksandra; Freiberg, Matthew S; Goetz, Matthew Bidwell; Rodriguez-Barradas, Maria C; Brown, Sheldon T; Crothers, Kristina A
Abstract: Objective: Tobacco use/smoking for epidemiologic studies is often derived from electronic health record (EHR) data, which may be inaccurate. We previously compared smoking from the United States Veterans Health Administration (VHA) EHR clinical reminder data with survey data and found excellent agreement. However, the smoking clinical reminder items changed October 1, 2018. We sought to use the biomarker salivary cotinine (cotinine ≥30) to validate current smoking from multiple sources. Materials and Methods: We included 323 Veterans Aging Cohort Study participants with cotinine, clinical reminder, and self-administered survey smoking data from October 1, 2018 to September 30, 2019. We included International Classification of Disease (ICD)-10 codes F17.21 and Z72.0. Operating characteristics and kappa statistics were calculated. Results: Participants were mostly male (96%), African American (75%) and mean age was 63 years. Of those identified as currently smoking based on cotinine, 86%, 85%, and 51% were identified as currently smoking based on clinical reminder, survey, and ICD-10 codes, respectively. Of those identified as not currently smoking based on cotinine, 95%, 97%, and 97% were identified as not currently smoking based on clinical reminder, survey, and ICD-10 codes. Agreement with cotinine was substantial for clinical reminder (kappa = .81) and survey (kappa = .83), but only moderate for ICD-10 (kappa = .50). Discussion: To determine current smoking, clinical reminder, and survey agreed well with cotinine, whereas ICD-10 codes did not. Clinical reminders could be used in other health systems to capture more accurate smoking information. Conclusions: Clinical reminders are an excellent source for self-reported smoking status and are readily available in the VHA EHR. Lay Summary: The Veterans Health Administration (VHA) changed the questions used to screen for tobacco use/smoking at routine clinic visits in October 2018. The tobacco use/smoking data from clinic visits prior to October 2018 was shown to agree well with confidentially self-reported cigarette smoking survey data, and the new questions beginning in October 2018 should result in even better agreement. Nonetheless, the new clinic questions needed to be evaluated and we were able to validate them using the biomarker cotinine, which detects nicotine in saliva for up to 4 days, as the "gold standard." We also compared cigarette smoking survey data and electronic health record diagnostic codes to cotinine. To identify current smoking, clinic questions and survey agreed well with cotinine (of those identified with tobacco use based on cotinine, 86% and 85% reported current tobacco use at clinic visits, and on the survey, respectively). Of those identified with tobacco use based on cotinine, only 51% had a diagnostic code for tobacco use. Tobacco use collected at VHA clinic visits is accurate, and this is important for identifying those who would benefit from tobacco use interventions and lung cancer screening.